(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The integration of cultural components such as customs, traditions, and media into language lessons plays a vital role in developing both language comprehension and cultural awareness among learners. These elements help students understand not only the linguistic structure of a language but also the social and cultural context in which it is used. Incorporating cultural aspects fosters more meaningful learning experiences, strengthens intercultural communication skills, and enhances learners’ motivation and engagement. This article examines the benefits and methods of embedding cultural elements into language instruction and highlights their significance in fostering a holistic understanding of the language